Theranostic Applications of Taurine-Derived Carbon Dots in Colorectal Cancer: Ferroptosis Induction and Multifaceted Antitumor Mechanisms - Zhang R; Lan S; Jia M; Liu F; Wang M; Jin Q; Su L; Liu G (International Journal of Nanomedicine)
Rongrong Zhang,1,* Shuting Lan,1,* Mengxuan Jia,1,* Fangyuan Liu,1 Mengqi Wang,2 Qin Jin,3 Liya Su,1 Gang Liu1 1Clinical Medicine Research Center, Affiliated Hospital of Inner Mongolia Medical University, Hohhot, Inner Mongolia, People’s Republic of China; 2College of Life Science and Oceanography, Weifang University, Weifang, Shandong, People’s Republic of China; 3Department of Pathology, Affiliated Hospital of Nantong University, Nantong, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gang Liu, Email 20190043@immu.edu.cnIntroduction: The theranostic potential of taurine-derived carbon dots (Tau/CDs) in colorectal cancer (CRC) remains largely unexplored, despite their promising physicochemical and biological properties.Methods: In this study, Tau/CDs were synthesized via a microwave-assisted irradiation method, employing citric acid as the carbon source, urea as the nitrogen source, and taurine (Tau) as the dopant. Comprehensive physicochemical characterization and biocompatibility assessments were performed both in vitro and in vivo. The anti-cancer efficacy of Tau/CDs against CRC was systematically evaluated through a series of functional assays, including cell viability, proliferation, migration, invasion, adhesion, clonogenicity, cell cycle progression, apoptosis, epithelial-mesenchymal transition (EMT), and transcriptomic profiling. The therapeutic efficacy was further validated in vivo using CRC xenograft murine models.Results: Tau/CDs exhibited excellent biocompatibility and significantly impaired key malignant properties of CRC cells, including viability, proliferation, migration, invasion, clonogenicity, and EMT. Treatment with Tau/CDs induced cell cycle arrest and apoptosis in vitro, while in vivo administration robustly suppressed tumor growth in xenograft models. Mechanistically, transcriptomic analysis combined with ferroptosis profiling identified Heme Oxygenase 1 (HO-1)-mediated ferroptosis as a critical pathway underlying the anti-tumor activity of Tau/CDs.Conclusion: Microwave-assisted synthesis of Tau/CDs from citric acid, urea, and Tau yielded biocompatible nanoparticles with potent anti-cancer properties. Tau/CDs were shown to inhibit CRC progression by regulating multiple malignant phenotypes, with HO-1-mediated ferroptosis emerging as a critical mechanistic axis. These findings highlight Tau/CDs as a promising candidate for future clinical translation in CRC nanomedicine.Keywords: taurine, carbon dots, colorectal cancer, ferroptosis, HO-1